Studies of Dust Properties in Sub−Structures around White Dwarf WD 0307+077 in IRIS Survey - Paudel, M. S. (Journal of Nepal Physical Society, 2022)
A huge dust structure of size 3° ×3° consisting of many sub−structures of dust nebulae and dust cavities is discovered around the WD 0307+077, located at RA (ICRS): 47.59° , DEC (ICRS): +7.84° , in far−infrared image of IRIS survey. Infrared flux density at 60 µm and 100 µm are used to calculate dust color temperature and dust mass in dust structure and all sub−structures. The contour plot is used to visualize the variation of infrared flux, dust color temperature and dust mass within all sub−structures. The inclination angle of isolated region of sub−structures is calculated to know the shape of the dust cloud. It is found that the dust color temperature of all the nebulae and cavities lies between the 20 K to 24 K, with range not more than 3 K. This range of temperature suggests that the sub−structures are moving towards the thermal stability. The dust mass shows the similar mass composition within all sub−structures, with variation of just one order magnitude. The linear regression shows a very good linear relation between between the infrared flux at 60 µm and 100 µm wavelength with regression coefficient more than 0.90 in five sub−structures and more than 0.78 in remaining two. The inclination angle of shows the all sub−structures are clearly edge−on in shape having inclination angle i > 45° . The Gaussian distribution of dust color temperature in all sub−structures shows more or less deviation from Normal distribution, the background sources observed in the SIMBAD database are suspected for this deviation.